2019
DOI: 10.1016/j.rse.2019.111260
|View full text |Cite
|
Sign up to set email alerts
|

Global mapping of soil salinity change

Abstract: Soil salinity increase is a serious and global threat to agricultural production. The only database that currently provides soil salinity data with global coverage is the Harmonized World Soil Database, but it has several limitations when it comes to soil salinity assessment. Therefore, a new assessment is required. We hypothesized that combining soil properties maps with thermal infrared imagery and a large set of field observations within a machine learning framework will yield a global soil salinity map. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
206
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 369 publications
(213 citation statements)
references
References 28 publications
5
206
0
2
Order By: Relevance
“…On the contrary, the average precision of feature space model that contained MSAVI was the worst with R 2 = 0.80. This above conclusions were consistent with the studies of Ivushkin et al [3] and Guo and Wen [7]. The reason was that the salinity would precipitate out of the surface soil, which apparently affected the surface albedo [2], [34], [32]- [36].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…On the contrary, the average precision of feature space model that contained MSAVI was the worst with R 2 = 0.80. This above conclusions were consistent with the studies of Ivushkin et al [3] and Guo and Wen [7]. The reason was that the salinity would precipitate out of the surface soil, which apparently affected the surface albedo [2], [34], [32]- [36].…”
Section: Resultssupporting
confidence: 91%
“…Scudiero et al [23] applied the linear modeling of remote sensing vegetation indices to explore the potentials of assessing soil salinity. Ivushkin et al [3] produced a global soil salinity map by combining thermal infrared images, soil texture data and field observations with machine learning method. Wang et al [24] conducted the detailed comparison in monitoring salinization between Sentinel-2 MSI and Landsat 8 image and found that MSI image performed better than Landsat 8 image.…”
Section: Introductionmentioning
confidence: 99%
“…Soil salinization is recognized as one of the most serious threats to agricultural production [ 1 ], affecting more than one billion hectares worldwide [ 2 ]. Increased salinization is expected to affect 50% of arable land by the year 2050 [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The rise in salt-affected soils could be due to an excess of soluble salts known as saline soils, while the supremacy of exchangeable sodium (Na + ) in soil is termed as sodic soils, or a mixture of both situations is called saline-sodic soils [ 2 ]. According to an estimate, the increase in the total area of salt-affected land from 1986 to 2016 was around 1 billion hectares [ 3 ]; that might be due to low rainfall, high evapotranspiration, defective drainage, and/or the successive application of fertilizers, soil amendments, and irrigation water having high salt contents [ 4 ].…”
Section: Introductionmentioning
confidence: 99%